Applications of susceptibility-based brain imaging using 7T MRI - Ali, Mobeen (2019)
MRI is a powerful non-invasive technique for imaging soft tissues and for providing information on chemical composition. In this thesis, the effects of magnetic susceptibility from iron contained in ferritin and haemoglobin, and of myelinated tissue were studied. These effects were measured using a range of imaging techniques, including susceptibility weighted imaging (SWI) and quantitative susceptibility mapping (QSM).